A Simple Method for Analysis of Titration Curves of Polyprotic Acids - A. Khan, A. S. (The Nucleus, 2015)
In the present work, the titration curves of polyrpotic acid were analyzed theoretically on the basis of general equilibrium constants expression for evaluation of formation and dissociation constants. The present work provides more insight into the analysis of titration curves and development of distribution diagrams. The formation-dissociation curves of oxalic acids were also analyzed for finding a general relation between formation and dissociation process. It was concluded that the present method of treatment of titration curves is applicable to analyze the complex acid-base equilibria.